Social enterprise in Asia theory, models and practice - Bidet, Éric, 1966-; Defourny, Jacques (Routledge Studies in Social Enterprise and Social Innovation., 2019)
"These SE models reveal or confirm an overall trend towards new ways of sharing the responsibility for the common good in today's economies and societies. We tend to consider as good news the fact that social enterprises actually stem from all parts of the economy. Indeed, societies are facing many complex challenges at all levels, from the local to the global level. The diversity and internal variety of SE models are a sign of a broadly shared willingness to develop appropriate--although sometimes embryonic--responses to these challenges, on the basis of innovative economic/business models driven by a social mission. In spite of their weaknesses, social enterprises may be seen as advocates for and vehicles of the general interest across the whole economy. Of course, the debate about privatisation, deregulation and globalised market competition--all factors that may hinder efforts in the search for the common good-has to be addressed as well. The first of a series of four ICSEM books, Social Enterprise in Asia will serve as a key reference and resource for teachers, researchers, students, experts, policy makers, journalists and other categories of people who want to acquire a broad understanding of the phenomena of social enterprise and social entrepreneurship as they emerge and develop across the world"--